First-in-human phase I/II, open-label study of the anti-OX40 agonist INCAGN01949 in patients with advanced solid tumors. Issue 10 (31st October 2022) - Davis, Elizabeth J; Martin-Liberal, Juan; Kristeleit, Rebecca; Cho, Daniel C; Blagden, Sarah P; Berthold, Dominik; Cardin, Dana B; Vieito, Maria; Miller, Rowan E; Hari Dass, Prashanth; Orcurto, Angela; Spencer, Kristen; et al.
Abstract : Background: OX40 is a costimulatory receptor upregulated on antigen-activated T cells and constitutively expressed on regulatory T cells (Tregs). INCAGN01949, a fully human immunoglobulin G1κ anti-OX40 agonist monoclonal antibody, was designed to promote tumor-specific immunity by effector T-cell activation and Fcγ receptor-mediated Treg depletion. This first-in-human study was conducted to determine the safety, tolerability, and preliminary efficacy of INCAGN01949. Methods: Phase I/II, open-label, non-randomized, dose-escalation and dose-expansion study conducted in patients with advanced or metastatic solid tumors. Patients received INCAGN01949 monotherapy (7–1400 mg) in 14-day cycles while deriving benefit. Safety measures, clinical activity, pharmacokinetics, and pharmacodynamic effects were assessed and summarized with descriptive statistics. Results: Eighty-seven patients were enrolled; most common tumor types were colorectal (17.2%), ovarian (8.0%), and non-small cell lung (6.9%) cancers. Patients received a median three (range 1–9) prior therapies, including immunotherapy in 24 patients (27.6%). Maximum tolerated dose was not reached; one patient (1.1%) receiving 350 mg dose reported dose-limiting toxicity of grade 3 colitis. Treatment-related adverse events were reported in 45 patients (51.7%), with fatigue (16 (18.4%)), rash (6 (6.9%)), and diarrhea (6 (6.9%)) being most frequent. One patient (1.1%) with metastatic gallbladder cancer achieved a partial response (duration of 6.3 months), and 23 patients (26.4%) achieved stable disease (lasting >6 months in one patient). OX40 receptor occupancy was maintained over 90% among all patients receiving doses of ≥200 mg, while no treatment-emergent antidrug antibodies were detected across all dose levels. Pharmacodynamic results demonstrated that treatment with INCAGN01949 did not enhance proliferation or activation of T cells in peripheral blood or reduce circulating Tregs, and analyses of tumor biopsies did not demonstrate any consistent increase in effector T-cell infiltration or function, or decrease in infiltrating Tregs. Conclusion: No safety concerns were observed with INCAGN01949 monotherapy in patients with metastatic or advanced solid tumors. However, tumor responses and pharmacodynamic effects on T cells in peripheral blood and post-therapy tumor biopsies were limited. Studies evaluating INCAGN01949 in combination with other therapies are needed to further evaluate the potential of OX40 agonism as a therapeutic approach in patients with advanced solid tumors. Trial registration number: NCT02923349 .